On the role of market makers for money market liquidity and tensions - Falko Fecht; Stefan Reitz; Patrick Weber (Kiel Institute for the World Economy (IfW), 2015)
We analyze the trading book of a key market maker in the European unsecured money market and study the extent to which liquidity risks accumulated by this market maker affect his pricing of liquidity and the bid/ask spread he quotes on unsecured borrowing and lending. We find that the larger the funding liquidity risk assumed by the market maker is, the higher the market price for liquidity. Furthermore, his bid/ask spread and the sensitivity of his bid/ask spread to the maturity of the transaction increases as his assumed liquidity risk rises. Our findings have two important implications: First, we document that the funding constraints and funding risks of market makers affect market liquidity in line with Gromp and Vayanos (2004) and Brunnermeier and Pedersen (2009) also in the unsecured money market. Second, we document that the retained liquidity risks of money market makers led to an economically significant rise in the unsecured to secured money market rates and contributed to the dry-up of this market in 2007/2008.
Keywords: G01; G10; G21; 330; Funding liquidity risk and money market liquidity; Liquidity constraints; Money market makers; Liquidity spirals